2016
DOI: 10.1016/j.jgr.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals that the protective effects of ginsenoside Rb1 are associated with the actin cytoskeleton in β-amyloid-treated neuronal cells

Abstract: BackgroundThe ginsenoside Rb1 (Rb1) is the most abundant compound in the root of Panax ginseng. Recent studies have shown that Rb1 has a neuroprotective effect. However, the mechanisms underlying this effect are still unknown.MethodsWe used stable isotope labeling with amino acids in cell culture, combined with quantitative mass spectrometry, to explore a potential protective mechanism of Rb1 in β-amyloid-treated neuronal cells.ResultsA total of 1,231 proteins were commonly identified from three replicate expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…To investigate the mechanisms associated with the neuroprotective activity of Rg1 in AD, we performed a comparative proteomic analysis of SH-SY5Y cells, which were treated with Rg1 after Aβ exposure using nano-LC-MS/MS combined with SILAC. We cultured SH-SY5Y cells in either light SILAC medium containing 12 C 6 -Arg and 12 C 6 , 14 N 2 -Lys or heavy medium containing 13 C 6 -Arg and 13 C 6 , 15 N 2 -Lys to label the cells with the stable isotopes [18] . Previous studies have shown that fresh and aged Aβ 25–35 decreases the cell survival rate based on the results of the MTT reduction assay [21] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the mechanisms associated with the neuroprotective activity of Rg1 in AD, we performed a comparative proteomic analysis of SH-SY5Y cells, which were treated with Rg1 after Aβ exposure using nano-LC-MS/MS combined with SILAC. We cultured SH-SY5Y cells in either light SILAC medium containing 12 C 6 -Arg and 12 C 6 , 14 N 2 -Lys or heavy medium containing 13 C 6 -Arg and 13 C 6 , 15 N 2 -Lys to label the cells with the stable isotopes [18] . Previous studies have shown that fresh and aged Aβ 25–35 decreases the cell survival rate based on the results of the MTT reduction assay [21] .…”
Section: Resultsmentioning
confidence: 99%
“…SILAC was performed as previously reported [18] . Briefly, SH-SY5Y cells were cultured for at least five cell divisions in either light SILAC medium containing 12 C 6 -Arg and 12 C 6 , 14 N 2 -Lys or heavy SILAC medium containing 13 C 6 -Arg and 13 C 6 , 15 N 2 -Lys supplemented with 10% dialyzed fetal bovine serum, 50 IU/mL penicillin, and 50 mg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings indicated that ginseng exhibits its neuroprotective properties and improves is could be due to the presence of bioactive compound ginsenosides in ginseng. Several studies have reported on the neuroprotective effect of ginsenosides, particularly ginsenosides Rg1, in various neurodegeneration models [157][158][159][160][161][162][163][164][165][166][167][168][169].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…The most attractive characteristic of Rb1 is its ability to modulate the cardiovascular system, wherein it can regulate arrhythmias and promote the release of catecholamines to invigorate the heart ( Wang et al, 2008 ). In addition, Rb1 can regulate the expression of actin cytoskeleton-related proteins to protect against AS and has been reported to inhibit inflammation and ameliorate insulin resistance under ER stress conditions ( Chen W. et al, 2016 ; Hwang et al, 2016 ). However, no studies have highlighted the protective effects of Rb1 on TNF-α-induced endothelial cell injury, and the mechanisms underlying these effects have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%